Agriculture and the environment in Poland in the years 1944–2004: an Outline - Janicki, Tadeusz (Studia Historiae Oeconomicae, 2024)
Among the many studies on the history of Polish countryside and agriculture after 1945, there are no studies analyzing in a broader scope the issue of the relationship between agricultural production and the natural environment, despite the close connection between this sector of the economy and natural resources. The negative impact of agricultural intensification based on chemicalization and mechanization of agriculture on the condition of the natural environment is also omitted (or treated marginally). This text is an attempt to fill this gap. Its subject is the problem of the impact of agriculture on the natural environment in Poland in the years 1944–2004, i.e. in the period from the end of the war to Poland’s accession to the European Union. The basic research questions concern the directions of agricultural policy in the above period and selected methods of agricultural intensification and their impact on the environment, with particular emphasis on artificial fertilization and chemical plant protection, agricultural mechanization and agricultural land improvement. Due to the lack of space, the description of the above problems is a synthetic sketch concerning selected issues that await in-depth research. However, existing research shows that the degree of environmental threat depends on the level of fertilization and use of plant protection products, the degree of mechanization and dissemination of monocultures, and the level of drainage. Therefore, in Poland it occurred with varying intensity, greater in large-scale farming areas and less in the case of small and extensive family farms.